Man and the homeland in the products of GeRshon Shofman - Ali, Baydaa Abbas (Al-Adab Journal, 2019)
The Jewish writer Gershon Shofman, born in Russia in 1880 and he died in Palestine in 1972, has ridiculed most of his literary productions, especially his stories, to show the role of man in his society and the suffering of the conflict and the difficulties of life. Shofman also shed light on the role of man in the building of the nation. In this context, Schofman used the meaning of the homeland, the homeland of the intended Jews, where he sometimes spoke directly and indirectly indirectly. The aim of all this is to encourage Jews, especially Eastern European Jews, to immigrate to their homeland. In most of his stories, Shofman focused on the events that took place in the Jews since the 1905 events in Russia and the failed revolution there, as well as the events of the First and Second World Wars, the war between Jews and Arabs and the establishment of the State of Israel. Shofman also discussed the subject of the escape of man from his homeland, especially the Jewish man and his transfer from one country to another in vain. The result was his migration to the Promised land.